Analisis Kesalahan dalam Menyelesaikan Soal Matematika Berbasis PISA Konten Change and Relationship pada Siswa Kelas VIII SMP Negeri 4 Surakarta Semester Gasal Tahun Ajaran 2015/2016 - Wati, Erna Hartika (2016)
Mathematics education is one of the most important in the world the essence of education whose development is growing rapidly, both material and role. Scale international assessment PISA, demonstrating mathematics achievement in Indonesia are far behind other countries, including the assessment results in change and relationships content or algebra PISA. Low math achievement is inseparable from the learning process in schools. Detailed error analysis is needed in order errors and the causes can be determined to minimize errors that can be improved mathematics achievement. This research aimed to describe, calculate the percentage and to find out the factor causing of students error in solving math problems based PISA the change and relationship content. This research is a qualitative descriptive. The subjects of research were VIIIC grade students of SMP Negeri 4 of Surakarta totaling 29 students. Data collection techniques using tests, interviews and documentation. Data validation was done by triangulation method by comparing the data of the test method, interview and documentation. Technique of analyzing data used included data reduction, data presentation, verification and conclusion drawing. An analysis framework was developed based on Newman's error categories. The results of research were obtained 4 types of errors and the percentage for each type of error, were comprehension errors 55,50%, transformation errors 27,75%, processing errors 6,28% and 10,47%. The results showed that comprehension errors and transformation is the more dominant errors than the other error. In general, the factors causing the error is reasoning ability and skills of students who are low in the problems solving on real context and manipulating it into algebraic form. The most influential factor is the students are not accustomed to using the troubleshooting process correctly according to step Polya.